Role of ambulatory glucose profile in identifying and managing a patient with disparity between FPG, PPG and HbAlc levels: a case report - Saboo, Banshi (International Journal of Research in Medical Sciences, 2020)
This case report describes the management of a patient with mismatch/disparity between his Fasting Plasma Glucose (FPG)/ Postprandial Glucose (PPG) levels with that of Glycosylated Haemoglobin (HbA1c) levels. This 43-year-old male patient with Type 2 Diabetes Mellitus (T2DM) was presented with increased urination and tiredness, especially in the evening hours, along with a tingling sensation in bilateral feet on and off, with leg pain since past 4 months. The patient was obese with a family history of cardiovascular disease. In this patient, SGLT2 inhibitors were found to be effective in addressing glycaemic variability without triggering hypoglycaemic risk. Continuous glucose monitoring system aided in understanding the blood glucose fluctuations caused by the diet. This case study indicated that careful evaluation and appropriate management using Ambulatory Glucose profile would aid in preventing complications in such patients and improve the overall clinical outcomes.